COMPARATIVE SKILLS TO COMMUNICATE SCIENCE STUDENTS USING GROUP INVESTIGATION LEARNING MODEL GENUINE OBJECT AND NON GENUINE OBJECTS IN SCIENCE SUBJECT - Alvy Nur Latifah Sari; Munkhmaral Tumennasan (Science Education, Institut Agama Islam Negeri Ponorogo, 2020)
Along with the times, humans are required to master the skills of communication, collaboration, critical thinking, and creativity. Communication skills become one of the important skills that must be mastered by someone. In this case the world of education plays a role in being able to train students to have communication skills. One of them is by applying the Group Investigation learning model assisted by Genuine Object, because with direct learning supported by real object media, students will easily make observations, and communicate everything they get. The objectives of this study are: 1) Knowing the difference in students' science communication skills with the Genuine Object and Non-Genuine Group Investigation learning models The sample used was one of class in Ponorogo District. Data used collecteddescriptive analysis were analyzed through descriptively quantitative and inferential statistics. The results showed that students 'science communication skills using Genuine Object Assisted Group Investigation learning models had an average value of 65.7 while students' communication communication skills using Group Investigation Non Genuine Objects had average values an average of 41.6. Communication skills of students using the Group Investigation learning model assisted by Genuine Object are better than Non Genuine Object. Based on the one tailed t test, the value obtained is - 3,27748. Based on the results of the study it can be concluded that the learning model of Group Investigation assisted by Genuine Object can improve students' science communication skills.